2020
DOI: 10.1007/s12038-020-00081-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of crops for insect resistance: An overview

Abstract: Phytophagous insect incidence is a serious threat for reduction of crop productivity globally. There is an estimation of one fourth of crop is being destroyed by insects annually. Indeed, the development of insectresistant crops is a great milestone in agriculture to increase crop yield and reduce pesticide dependency. Genetic engineering facilitates development of insect resistant crops by expressing bacterial d-endotoxins and vegetative insecticidal proteins and other plant genes like lectins, protease inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 62 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Alpha-amylase (α-Amylase) is an enzyme that can hydrolyze α-D- (1,4)-glycosidic bonds in starch or polysaccharides. Starch and polysaccharides must be hydrolyzed into disaccharides and oligosaccharides which are then hydrolyzed by the α-glycosidase enzyme to monosaccharide molecules that are absorbed into the hepatic portal vena via the small intestine .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-amylase (α-Amylase) is an enzyme that can hydrolyze α-D- (1,4)-glycosidic bonds in starch or polysaccharides. Starch and polysaccharides must be hydrolyzed into disaccharides and oligosaccharides which are then hydrolyzed by the α-glycosidase enzyme to monosaccharide molecules that are absorbed into the hepatic portal vena via the small intestine .…”
Section: Introductionmentioning
confidence: 99%
“…Almost one-fourth of global crops are destroyed by insects annually . [4] Some larvae rely on the starch in crops, against which amylase inhibitors in plants provide some defense . [5] Research [6] has shown that the expression profiles of important DNA repair genes in bone marrow stem cells are negatively affected by the genotoxicity of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of studies have shown the feasibility of transgenic crops protecting plants against pests and pathogens ( Baum et al, 2007 ; Mao et al, 2011 ; Pitino et al, 2011 ; Zha et al, 2011 ; Zhang et al, 2015 ; Malik et al, 2016 ; Yu et al, 2016 ; Khalid et al, 2017 ; Li et al, 2017 ). Transgenic crop protection has also been reviewed in a number of publications ( Talakayala et al, 2020 ; Chung et al, 2021 ; Kumari et al, 2022 ). The main advantage associated with in planta dsRNA synthesis (endogenous dsRNA production) in comparison to alternative production systems, is the elimination of downstream processing, with no purification, formulation and/or delivery of the dsRNA or material containing the dsRNA required, thus reducing labour for agricultural workers and consequently reducing costs to the consumer ( Zotti and Smagghe, 2015 ).…”
Section: Strategies For Production Of Dsrna For Crop Protectionmentioning
confidence: 99%
“…The different biotechnological approaches include gene transformation, genome editing, RNA interference, marker-assisted selection, anther culture, embryo culture, protoplast fusion, somaclonal variations etc. ( Talakayala et al, 2020 ). These approaches are described in detail below.…”
Section: Biotechnological Approaches In Insect Pest Managementmentioning
confidence: 99%